EFEKTIVITAS ISOLAT Actinomycetes DARI SAMPEL TANAHKEBUN RAYA BOGOR DALAM MENGHAMBAT PERTUMBUHAN Salmonella typhi SECARA IN VITRO - Rayhan Maulana, (2019)
Actinomycetes are a group of antibiotic-producing bacteria, mainly from the Genus Streptomyces. Actinomycetes produce secondary metabolites that have the same function as antibacterial. Salmonella typhi is a pathogenic bacterium that produces endotoxins as a component in the pathogenicity of infectious diseases such as typhoid fever. Actinomycetes produces secondary metabolism that has potential to inhibit the growth of S.typhi. The purpose of this research is to find out the effectiveness of Actinomycetes in inhibiting S.typhi growth in vitro. This research had used experimental design with Actinomycetes samples originating from Kebun Raya Bogor wells diffusion method using Muller Hinton Agar (MHA) media that had been used for viewing clear zone of bacterial growth. The results of this study had shown the presence of clear zones of 3 dilution series 10 -4 , 10 -5 , 10 -6 to the growth of S.typhi with average diameter were 12.7 mm; 11.8 mm; and 11.7 mm, respectively. One Way Anova test results (α = 0.05) showed that there was a significant difference between each concentration of S.typhi. This research showed that Actinomycetes colony contains active compounds in the form of streptomycin, gentamicin, tetracycline, vancomycin, erythromycin as an antibacterial which can inhibit S.typhi protein synthesis